2020
DOI: 10.1145/3373759
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intelligent Voice Assistants by Older Adults with Low Technology Use

Abstract: Voice assistants embodied in smart speakers (e.g., Amazon Echo, Google Home) enable voice-based interaction that does not necessarily rely on expertise with mobile or desktop computing. Hence, these voice assistants offer new opportunities to different populations, including individuals who are not interested or able to use traditional computing devices such as computers and smartphones. To understand how older adults who use technology infrequently perceive and use these voice assistants, we conducted a 3-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(107 citation statements)
references
References 62 publications
3
103
0
1
Order By: Relevance
“…The practical scenarios show that Alexa has difficulties in understanding the project’s name and the user name. This is the case in other research papers as well, especially in the medical field [ 29 , 53 ]. In this point, we wanted to further understand which is the users’ perception of the implemented Alexa skills, in this way answering (RQ3).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The practical scenarios show that Alexa has difficulties in understanding the project’s name and the user name. This is the case in other research papers as well, especially in the medical field [ 29 , 53 ]. In this point, we wanted to further understand which is the users’ perception of the implemented Alexa skills, in this way answering (RQ3).…”
Section: Resultsmentioning
confidence: 60%
“…A distinct application category is that of employing VAs to help the elderly that have visual impairment [ 24 , 25 ], need strengthening of social bonds [ 26 ], or daily caring [ 27 , 28 ]. In [ 29 ], Amazon Echo Dot was used in the home of seven older adults. This VA was consistently used for finding online health-related information, while the usage of other features, like setting timers, reminders, and so on, was low due to reliability issues.…”
Section: Previous Workmentioning
confidence: 99%
“…Lastly, research has explored the utility and usability of voice assistants as an assistive technology [ 21 , 22 ]. In particular, researchers are increasingly recognizing the potential that voice assistants can offer in the aging society [ 5 , 23 ], exploring application areas to facilitate voice assistants to support older adults [ 24 , 25 ]. This paper contributes to this emerging body of literature by specifically investigating the first reactions that older adults have to voice assistants.…”
Section: Introductionmentioning
confidence: 99%
“…Their use has opened new possibilities for a wide range of people—including elderly adults who otherwise have no interest or expertise in technological devices. However, data reported about their use seem ambivalent: while a number of studies have argued their efficiency in healthcare due to their use of natural language and ability to simulate human conversations [ 87 , 89 , 90 ], others have suggested that interactions through these kinds of devices are inconsistent and incomplete [ 91 , 92 ], which can have dangerous consequences. In order to improve these issues, researchers are developing specific skills or applications to help integrate the medical agenda, prescription reminders, and other healthcare monitoring systems into existing devices [ 93 ].…”
Section: Discussionmentioning
confidence: 99%